تأثير الاتفاقيات الدولية على حقوق المرأة في الدول النامية - عبد القادرأ. فائزة أحمد محمد (Aljameai, 2025)
المستخلص: تتناول هذه الدراسة تأثير الاتفاقيات الدولية على حقوق المرأة في الدول النامية، مع التركيز على كيفية تطبيقها ودورها في تحسين أوضاع المرأة. تُظهر الدراسة أن الاتفاقيات الدولية مثل اتفاقية القضاء على جميع أشكال التمييز ضد المرأة (CEDAW) قد ساهمت في تطوير بعض التشريعات الوطنية لتحسين مكانة المرأة وتعزيز حقوقها. ومع ذلك، فإن التنفيذ يواجه تحديات عديدة، أبرزها ضعف الإرادة السياسية، التأثير السلبي للعادات والتقاليد، ونقص الموارد. توضح الدراسة حالات نجاح محدودة في بعض الدول النامية، بينما تسلط الضوء على الإخفاقات الناتجة عن غياب آليات فعالة للرصد والتنفيذ. وخلصت الدراسة إلى أن تحسين حقوق المرأة يتطلب التزامًا أقوى من الدول النامية وإصلاحات هيكلية تعزز المساواة الجندرية. Abstract: This study explores the impact of international agreements on women’s rights in developing countries, focusing on their implementation and role in improving women’s status. The findings highlight those international agreements, such As stated by the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW), have contributed to the development of national legislations aimed at enhancing women’s rights. However, implementation faces numerous challenges, including weak political will, the negative influence of cultural traditions, and resource constraints. While the study identifies some successful cases In developing countries, it also serves as highlights failures stemming from the absence of effective monitoring and enforcement mechanisms. The study concludes that advancing women’s rights requires stronger commitments from developing countries and structural reforms to promote gender equality.